Familial hypertrophic myocardiopathy - Lazo-Soldevilla, Marco (2021)
We present the case of a 16 year-old man with a diagnosis of hypertrophic cardiomyopathy and a history of sudden family death; risk stratification was performed using the clinical risk prediction model for patients with hypertrophic cardiomyopathy (HCM Risk -SCD), being a high-risk patient for which animplantable automatic defibrillator was placed as primary prevention.